Mission impossible? UN mediation in Libya, Syria and Yemen - Muriel Asseburg; Wolfram Lacher; Mareike Transfeld (Stiftung Wissenschaft und Politik (SWP), 2018)
The upheavals in the Arab world since 2011 have led to civil wars in three countries: Libya, Syria and Yemen. In all three cases, the United Nations have tried to mediate agreements between the conflicting parties to bring about peace through power-sharing. In this endeavour, the UN can lean on its broad experience in mediation efforts to end civil wars. In the three conflicts examined here, however, the UN's attempts at resolution through power-sharing have failed. In Yemen and Libya, power-sharing agreements have not prevented conflicts from lingering on or violence from breaking out again. In Syria, the UN has not even managed to bring together the Syrian parties in the civil war for direct talks. The altered military balance of power has rendered the initial goal of a political transition unrealistic. This study answers the following questions: Why are these three conflicts so resistant to resolution efforts? What are the specific aspects of the conflict configurations that impede UN efforts? What factors in the UN approach are obstacles to a successful conclusion? What lessons can be learned for future mediation efforts? And how can Europe contribute to progress in this area?
Keywords: 320; Machtteilung; Power sharing